2010
DOI: 10.4025/actasciagron.v32i2.3681
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos biométricos de frutos e sementes, grau de umidade e superação de dormência de jatobá

Abstract: RESUMO. Este trabalho objetivou caracterizar biometricamente sementes e frutos deHymenaea courbaril L. e determinar o grau de umidade, bem como avaliar diferentes tratamentos de superação de dormência. Foram determinados a biometria, a massa de frutos e sementes e o número de sementes por fruto. As sementes foram submetidas aos seguintes cortes: 1-testemunha, sem escarificação ou corte; 2-escarificação em três faces; 3-corte ao meio e 4-corte em quatro partes. Avaliou-se também o percentual de emergência, o IV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 17 publications
(13 reference statements)
1
4
0
3
Order By: Relevance
“…These results show that methods that do not allow for water permeation into the seed are ineffective. Similar results were also observed for the seeds of other species, such as the Jatobá or Brazilian Cherry (Hymenaea courbaril L.); the seeds of this tree present exogenous dormancy and an intact tegument before seeding, and these characteristics lead to a low percentage of germination (Andrade, Bruno, Oliveira, & Silva, 2010).…”
Section: Resultssupporting
confidence: 80%
“…These results show that methods that do not allow for water permeation into the seed are ineffective. Similar results were also observed for the seeds of other species, such as the Jatobá or Brazilian Cherry (Hymenaea courbaril L.); the seeds of this tree present exogenous dormancy and an intact tegument before seeding, and these characteristics lead to a low percentage of germination (Andrade, Bruno, Oliveira, & Silva, 2010).…”
Section: Resultssupporting
confidence: 80%
“…The morphological differences exhibited in the seminal structure are related to ecological functionality adapted to variations in environmental conditions (Andrade et al, 2010). Thus, the morphological suitability of seedlings to environmental conditions may interfere with the reproductive success of the species (Lobo, Santana, Salomão, Rehbein, & Wielewicki, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Tropical trees exhibit high variability regarding seed morphofunctional characteristics, since the absence or presence of energy reserves determine cotyledon function, which consequently affect seedling establishment and directly influence the successional dynamics of the species (Andrade, Bruno, Oliveira, & Silva, 2010). In this sense, it is necessary to expand studies including silvicultural information on forest species, because according to Ribeiro et al (2009), rational management based on scientific, social and economic interest depends on the knowledge of the regenerative and productive capacity of forests.…”
Section: Introductionmentioning
confidence: 99%
“…Silva et al [34] presented a slightly wider range from 2.62 to 4.36 g. But consistent wider ranges could be found in Andrade et al [35], which found seeds from 4.08 to 11.2g. Those last authors also mention that moisture content could also be responsible for the variations between seed mass, which was still indicated in other previous studies [36].…”
Section: Page|mentioning
confidence: 53%
“…Tropical arboreous species usually present a high variability in seed mass [4].Other studies mention that seed weight is highly variable due to the water content [35], which also varies according to some environmental conditions during seed development, and features, such as maturation stage [36], [37]. However, this species seed moisture content could vary between 12.46 until 16.05 % of the weight [37], a very strict range in view of the diversity of values found to seed weigh disposable in the literature, or even the present study variation.…”
Section: Page|mentioning
confidence: 99%